ROLE PLAYING GAME; UPAYA DALAM MENGATASI ANAK INTROVERT - Putri Arini (Educare : Jurnal Ilmu Pendidikan, 2022)
This study aims to analyze and examine the application of role playing games in overcoming introverted children in early childhood at RA Uswatun Hasanah, Maron, Probolinggo. This research uses a qualitative approach, while the type of research uses case studies. The data analysis technique uses data reduction, data display, and drawing conclusions or verification. The results showed that the teacher's steps in implementing Role Playing Games in overcoming the problems of introverted children through; Preparation and Planning Analysis, Role Playing Engineering, Activity Documentation, Activity Evaluation. This research has implications for the use of role playing, especially at RA Uswatun Hasanah, introverted children begin to be able to mingle and even adapt to their friends even though slowly.